The effectiveness of A suggested strategy based on the communicative approach in developing some speaking skills and values for preparatory stage students - Elshahat, Tarek Shehata Aly; Abdulaziz, Manal Mohammed; Zaher, Aida Abdel Maksoud (جامعة عين شمس - كلية البنات للآداب والعلوم والتربية, 2011)
تتحدد مشكلة البحث الحالي في ضعف مهارة التحدث وضعف اكتساب القيم لدى طلاب الصف الثاني الإعدادي بالمدارس الحكومية ويرجع ذلك إلى عدم استخدام أنشطة وأساليب تدريس فعالة داخل حجرة الدراسة. \ وهكذا فقد كان هدف البحث الحالي هو دراسة أثر استخدام المدخل التواصلي في تنمية بعض مهارة التحدث والقيم لدى طلاب الصف الثاني الإعدادي بمدرسة الدلتا الإعدادي الأزهري. The present study aimed at investigating the effectiveness of a strategy designed in the light of the Communicative Approach techniques on second year preparatory students' learning of speaking skills and values. \ Two second year preparatory classes were randomly selected from Al Delta Al Azhary preparatory School for boys, in the the academic year 201O-2011,one class as an experimental group and the other as a control group .Students in the experimental group received instruction through the proposed strategy over a period of two months and a half ; While students in the control group received regular instruction. \ By the end of the treatment, speaking and values post-tests were administered to both the experimental and control groups. The results showed evidence that there was statistically significant difference between the mean scores of the experimental and control groups on speaking post-test at 0.01 level in favor of the experimental group .Similarly, the results showed evidence that there was statistically significant difference at 0.01 level between the mean scores of the experimental and control groups on the value post-test in favor of the experimental group. Besides, it showed improvement in the experimental group students' performance in the speaking and values pre-post tests in favor of the post-tests. It was concluded that the proposed strategy was effective in developing second year preparatory students' speaking skills and value.
Keywords: طرق التدريس -- تدريس اللغة الإنجليزية -- استراتيجيات التعلم -- تنمية المهارات -- مهارات القراءة -- طلاب المدارس المتوسطة